DISIPLIN KERJA TERHADAP EFEKTIFITAS KERJA PADA PT. BANK RAKYAT INDONESIA KANTOR CABANG LUBUKLINGGAU TAHUN 2015 - Rudi Azhar (El-Ghiroh : Jurnal Studi Keislaman, 2016)
This study assesses the effectiveness of Influence Work Discipline Work on PT.BPR Branch Lubuklinggau. The method used was a questionnaire method by using two (2) pieces of the questionnaire is a questionnaire work discipline and effectiveness. The magnitude of the effect of labor discipline (X) on the effectiveness of the work (Y) on PT.Bank Rakyat Indonesia Branch Lubuklinggau with regression calculation equation y = 19.9 + 0.45 X, then obtained tcount 1.78 and t table amounted to 1.701, This means that these variables work discipline and effectiveness in PT. Bank Rakyat Indonesia Branch Lubuklinggau jointly or overall significant effect. So the work discipline variable influential signifiakn the effectiveness of the work on the PT. Bank Rakyat Indonesia Branch Lubuklinggau, meaning that the work discipline variable (X) and variable effectiveness of work (Y) correlated.